Progress of ossification and epithelialization of wounds after simple or surgical extractions of teeth in rats with chronic renal failure: an experimental study - A. I. Mylonas,* G. B. Massoulas, O. Nicolatou, I. A. Dontas, L. Nakopoulou,C. J. Stefanidis (Blackwell Synergy, 2000)
Patients with renal disease are a challenge to oral and maxillofacial surgeons and general dental practitioners because there is a widespread opinion, particularly among surgeons, that CRF affects and complicates wound healing.1–5 Tooth extraction is the most common type of surgical wound in the oral and maxillofacial region, so if CRF impairs wound healing, it is important to study the progress of wound healing after extraction in the presence of moderate chronic renal insufficiency in a rat experimental model.